Mengenalkan dan Membelajarkan Matematika Pada Anak Usia Dini - Analisa Fitria (Universitas Islam Negeri Antasari Banjarmasin, 2013)
Mathematics has been quite familiar in our daily life. In the field of education, Mathematics is regularly presented from the elementary up to the higher education level. Nevertheless, Math seems like a haunting danger for most children. The data from The Third International in Mathematics and Science Study shows that in 2012 the Maths intelligence of Indonesian secondary students ranked at 34 of 38 nations being surveyed. Thus, it is necessary to start introducing Math to children since their early age. However, Introducing and teaching maths for children will be obviously different with that of the adults.